2019
DOI: 10.9734/ajarr/2019/v7i230169
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Assessment of Antidiabetic Potential and Mapping of Pharmacological Properties of Ethanolic Extract of Leaves of Coccinia grandis on Alloxan-induced Diabetic Rats

Abstract: Diabetes is a metabolic disease and plant derived products are used to combat this deadly disease. Plant is a diverse source of numerous therapeutic compounds which can be used to ameliorate diabetes. Leaves of Coccinia grandis (L.) (Family: Cucurbitaceae) is one of the leafy vegetable that is used for this purpose traditionally. It has been used against diabetes for a very long time. Our aims were to identify the hypoglycemic effect of extract of leaves of Coccinia grandis as well as to determine its safety p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…According to the findings of our study, it was observed that reduction in food intake had no effect on the blood glucose levels of rats. The damaging effects of alloxan-induced cellular atrophy and an initial weight loss in rats treated with alloxan [ 51 ]. However, when the rats (both nondiabetic and diabetic) were treated with test extract ( G. procumbens ), their body weights accelerated just like the rats belonging to other groups.…”
Section: Discussionmentioning
confidence: 99%
“…According to the findings of our study, it was observed that reduction in food intake had no effect on the blood glucose levels of rats. The damaging effects of alloxan-induced cellular atrophy and an initial weight loss in rats treated with alloxan [ 51 ]. However, when the rats (both nondiabetic and diabetic) were treated with test extract ( G. procumbens ), their body weights accelerated just like the rats belonging to other groups.…”
Section: Discussionmentioning
confidence: 99%
“…The ethanol Coccinia grandis leaves reported a non-significant hypoglycemic effect comparable to the standard drug metformin at 750 mg/kg dose [ 318 ]. Another report by Islam et al 2014 exhibited a substantial reduction in fasting blood glucose levels from C. grandis and Centella asiatica at a dose of 3 mL/kg in both normal and therapeutic models of alloxan-induced diabetic rats [ 319 ].…”
Section: Phytochemical and Experimental Studies Of Antidiabetic Plants In Bangladeshmentioning
confidence: 99%
“…In the 1 st two weeks, the rats were treated with normal food and water without inducing diabetes. Afterward, alloxan was injected into all group 150 mg/kg [19] via intraperitoneal route in all rats those belonged to group 2,3 and 4. Blood glucose levels of these rats were examined to confirm whether they have started suffering from diabetes or not.…”
Section: Groupmentioning
confidence: 99%